Copper alloy
A copper alloy with precise Ni, Si, Al, Sn, and B compositions and ratios ensures uniform precipitate dispersion, enhancing hardness and yield, addressing defects in production and use.
Patent Information
- Application Number
- JP2023147190
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2043-09-11
AI Technical Summary
Existing copper alloys without beryllium face issues such as rapid precipitation of large particles leading to material defects, disconnection, and breakage during production and use, particularly in contact probe pins, due to non-uniform dispersion of precipitates and low melting point elements like Sn causing grain boundary collection.
A copper alloy with specific compositions of Ni, Si, Al, Sn, and B, along with a defined relative ratio, ensuring Vickers hardness of 350 HV or more and electrical conductivity of 8% IACS or more, effectively dispersing precipitates for improved hardness and yield during mass production.
The alloy achieves high hardness, suppresses material loss over time, and maintains high yield during mass production, preventing defects like disconnection and breakage, suitable for contact probe pins and other applications requiring durability.
Smart Images

Figure 0007610667000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper alloy having a long shape such as a wire or a rod. [Background technology]
[0002] Beryllium copper has been known as a copper alloy having a high hardness of 350HV or more in Vickers hardness. Beryllium copper is widely used in applications requiring high hardness, such as contact probe pins used in semiconductor inspection, connector pins, and industrial high-speed sewing machine sliding shaft bearings. On the other hand, since beryllium has problems such as toxicity and availability, in recent years, copper alloys that do not contain beryllium are desired. For example, Patent Documents 1 and 2 have been proposed as copper alloys that do not contain beryllium. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5743165 [Patent Document 2] Patent No. 7145070 Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 1, Ni and Si precipitate quickly, and high hardness can be relatively easily achieved, but precipitates with large diameters tend to be generated. When such precipitates fall off the surface of the copper alloy, they cause material defects, such as wire breakage and breakage starting from the defect. In particular, when this type of copper alloy is used for the pin of a contact probe, the defect on the pin surface comes into contact with a silicon wafer, causing damage to the silicon wafer to be inspected. In addition, when the copper alloy of Patent Document 1 is processed to mass-produce a long-shaped product (a wire-shaped or rod-shaped product), there is a problem that the above-mentioned precipitates cause wire breakage and breakage during the production process, reducing the yield.
[0005] The copper alloy of Patent Document 2 contains Sn, which refines the precipitates and can solve the problems such as those in Patent Document 1. However, since Sn has a relatively low melting point, precipitates tend to accumulate at grain boundaries. For this reason, it is difficult for the precipitates to be uniformly dispersed in the grains, and there is room for improvement in terms of improving the hardness in the long-length form.
[0006] The present invention has been devised in view of the above circumstances, and an object thereof is to provide a long-length copper alloy that has high hardness, can suppress material loss over a long period of time, and has a good yield during mass production.
Means for Solving the Problems
[0007] The present invention is a long-length copper alloy having an equivalent wire diameter of 0.5 to 5.0 mm, and contains, in mass %, 9.00% ≦ Ni ≦ 15.00%, 0.30% ≦ Si ≦ 0.90%, 0.50% ≦ Al ≦ 2.00%, 2.00% < Sn ≦ 4.50%, 0% < B < 0.010%, with the balance being composed of Cu and unavoidable impurities, having a Vickers hardness of 350 HV or more, a conductivity of 8% IACS or more, and satisfying the relational ratio of Si, Al, Sn, and B: 120 ≦ (1.7Si + 1.2Al + Sn) / 3.9B ≦ 300.
[0008] The copper alloy of the present invention may contain, in mass %, 11.00% ≦ Ni ≦ 15.00%, 0.40% ≦ Si ≦ 0.90%, 1.00% ≦ Al ≦ 2.00%.
[0009] The copper alloy of the present invention may satisfy the relational ratio of 160 ≦ (1.7Si + 1.2Al + Sn) / 3.9B ≦ 250.
[0010] Any of the above copper alloys of the present invention may be used as a pin for a contact probe.
Effects of the Invention
[0011] By adopting the above configuration, the copper alloy of the present invention has high hardness, can suppress material loss over a long period of time, and has a good yield during mass production.
Brief Description of the Drawings
[0012] [Figure 1] It is a schematic cross-sectional view of a contact probe. [Diagram 2] It is an enlarged photograph of the tip of the pin for the contact probe of Comparative Material 1. [Diagram 3] It is an enlarged photograph of the tip of the pin for the contact probe of Comparative Material 2. [Figure 4] It is a cross-sectional photograph of the pin for the contact probe of Comparative Material 3. [Diagram 5] It is an enlarged photograph of the surface of the pin for the contact probe of Comparative Material 3.
Modes for Carrying Out the Invention
[0013] Hereinafter, some embodiments of the present invention will be described with reference to the drawings. It should be noted that the following embodiments and the specific configurations shown in the drawings are for understanding the content of the present invention, and the present invention is not limited to the specific configurations shown.
[0014] The copper alloy of the present embodiment is a long-shaped copper alloy with an equivalent wire diameter of 0.5 to 5.0 mm. By mass%, 9.00% ≤ Ni ≤ 15.00%, 0.30% ≤ Si ≤ 0.90%, 0.50% ≤ Al ≤ 2.00%, 2.00% < Sn ≤ 4.50%, 0% < B < 0.010% are included, and the balance is composed of Cu and inevitable impurities. The conductivity is 8% IACS or more, the Vickers hardness is 350 HV or more, and the relational ratio of Si, Sn, and B satisfies 120 ≤ (1.7Si + 1.2Al + Sn) / 3.9B ≤ 300. Hereinafter, these configurations will be described in detail.
[0015] [Equivalent Wire Diameter] The copper alloy of this embodiment is in a long form with an equivalent wire diameter of 0.5 to 5.0 mm. In this specification, the term "long form" refers to a thin and long wire, rod, or the like that can define the longitudinal direction and the direction of the cross section perpendicular thereto. The cross section of the long form is not limited to a circular shape, and may be a non-circular cross section such as an ellipse or a rectangle. In this specification, the term "equivalent wire diameter" refers to the diameter of the cross section when the cross section of the long form is a perfect circle, but when the cross section is a non-circular shape such as an ellipse or a rectangle, it refers to the diameter of a perfect circle that is equal to the area of the cross section. Copper alloys having such an equivalent wire diameter are suitable as product materials that require high hardness, such as contact probe pins, connector pins, and industrial high-speed sewing machine sliding shaft bearings.
[0016] 1 shows a schematic cross-sectional view of a contact probe 1. The contact probe 1 is used for testing electrical characteristics of ICs, wafers, sockets, etc. In a conductivity test, the tip of a pin 2 is brought into contact with a surface to be tested, and electrical characteristics at that surface are tested. The copper alloy of this embodiment is suitably used as a pin for such a contact probe.
[0017] In this embodiment, the reason why the amounts of each element are specified as above (unit: mass %) is as follows.
[0018] [Nickel (Ni)] Ni is added in an amount of 9.00% or more to combine with Si, Al, and Sn to precipitate Ni2Si, Ni3Al, and Ni3Sn2, thereby improving the hardness of the copper alloy. If the Ni content is less than 9.00%, the amount of combination with each of the above elements is also reduced, and high hardness cannot be obtained. From this viewpoint, Ni is preferably set to 11.00% or more. On the other hand, if the Ni content exceeds 15.00%, Ni is added in an amount that exceeds the amount that combines with Si, Al, and Sn, which may lead to a decrease in electrical conductivity. From this viewpoint, Ni content is preferably set to 13.00% or less.
[0019] [Silicon (Si)] Si is added in an amount of 0.30% or more in order to combine with Ni to precipitate Ni2Si and improve the hardness of the copper alloy. If the content of Si is low, the amount of combination with Ni decreases, and sufficient improvement in hardness cannot be obtained. From this viewpoint, the content of Si is preferably set to 0.40% or more. On the other hand, addition of a large amount of Si generates coarse Ni2Si compounds. Although this compound increases the hardness of the copper alloy, it may reduce the toughness of the copper alloy, and may cause wire breakage during wire drawing or the like. In addition, it may increase the risk of material chipping due to the falling off of coarse precipitates. From this viewpoint, the content of Si is set to 0.90% or less, but taking into account the effect of improving heat resistance, it is preferably set to 0.80% or less.
[0020] [Aluminum (Al)] Al is added in an amount of 0.50% or more in order to combine with Ni to precipitate Ni3Al or NiAl and improve the hardness of the copper alloy. If the content of Al is low, the amount of combination with Ni decreases, and sufficient improvement in hardness cannot be obtained. From this viewpoint, the content of Al is preferably 1.00% or more. On the other hand, addition of a large amount of Al generates an excessive amount of Ni3Al compound. Although this compound increases the hardness of the copper alloy, it reduces the toughness of the copper alloy, and may cause breakage during wire drawing or the like. From this viewpoint, the content of Al is set to 2.00% or less, but taking into account the effect of improving heat resistance, it is preferably set to 1.80% or less.
[0021] [Tin (Sn)] Sn is added in an amount of more than 2.00% in order to combine with Ni to precipitate Ni3Sn2 or Ni3Sn, thereby improving the hardness of the copper alloy, and to suppress the increase in the diameter of the precipitates (promoting fineness). If the Sn content is low, the amount of Sn combined with Ni decreases, and the effect of improving the hardness is not sufficient, and precipitates with relatively large diameters tend to precipitate. On the other hand, if a large amount of Sn is added, the excessive Sn reduces the strength of the crystal grain boundaries, which may cause material cracks during wire drawing or forging. From this viewpoint, the Sn content is set to 4.50% or less, preferably 3.50% or less.
[0022] [Boron (B)] B is added in an amount of more than 0%, preferably 0.003% or more, to improve corrosion resistance and to disperse precipitates such as Ni2Si, Ni3Al, and Ni3Sn2 more finely to further improve the hardness of the copper alloy. On the other hand, the addition of a large amount of B may not only reduce the toughness and workability of the copper alloy, but may also cause holes (so-called "cavities") in various places in the material. From this perspective, the B content is set to less than 0.010%, preferably 0.009% or less.
[0023] [Inevitable impurities] The copper alloy of this embodiment contains the above-mentioned component elements, with the remainder being composed of inevitable impurities and Cu. Examples of inevitable impurities include O, Zn, Mn, Fe, and S. In particular, O forms oxides that deteriorate plastic workability and reduce electrical conductivity, and S and Fe also form harmful coarse inclusions, so that the total content of these is preferably 0.20% or less. In addition, the content of each impurity is preferably about 0.10% or less.
[0024] [Relationship ratios of Si, Al, Sn and B] In order to improve the electrical conductivity and workability of the copper alloy, it is sufficient to increase the Cu content. On the other hand, in order to increase the hardness of the copper alloy, it is necessary to precipitate more Ni2Si, Ni3Al, NiAl, Ni3Sn2 and Ni3Sn in the copper alloy. The inventors have focused on the relative ratios of Si, Al and Sn to B (hereinafter, simply referred to as "relative ratios") in copper alloys having a long shape such as wires and bars, and conducted experiments with various different relative ratios. As a result, it has been found that, on the premise of the ranges of the contents of Si, Al and Sn described above, by specifying the relative ratio within a certain range, it is possible to simultaneously achieve the improvement of the hardness of the copper alloy due to the precipitation of precipitates and the suppression of the detachment and chipping of precipitates from the material surface during product processing and long-term use of the copper alloy. Specifically, it was found that when the value of the relationship ratio (1.7Si+1.2Al+Sn) / 3.9B is less than 120, the content of B becomes excessive relative to the contents of Si, Al, and Sn, which leads to a decrease in the toughness of the copper alloy, which causes breakage and fracture during the product processing process, and reduces the yield. On the other hand, when the value of the relationship ratio (1.7Si+1.2Al+Sn) / 3.9B exceeds 300, the content of B becomes insufficient relative to the contents of Si, Al, and Sn, and the precipitates of Ni2Si, Ni3Al, NiAl, Ni3Sn2, and Ni3Sn cannot be sufficiently dispersed. Furthermore, non-dispersion of precipitates in copper alloys in long shapes such as wires and rods causes defects due to the precipitates falling off due to continuous impact forces received during the product processing process and after the productization of the copper alloy. From the above viewpoints, the copper alloy of this embodiment specifies the relative ratio (1.7Si+1.2Al+Sn) / 3.9B to be in the range of 120 or more and 300 or less, and more preferably 160 or more and 250 or less.
[0025] [Vickers hardness (HV)] The copper alloy of this embodiment has a Vickers hardness of 350HV or more. The Vickers hardness is measured based on JIS-Z2244. The copper alloy of this embodiment is specified to have a Vickers hardness of 350HV or more as a hardness that can withstand processing into products and repeated use (impact force, etc.). If the Vickers hardness of the copper alloy is less than 350HV, it is not suitable for use in which a large impact force is repeatedly applied, such as a pin for a contact probe. From this viewpoint, the Vickers hardness of the copper alloy is preferably 380HV or more, more preferably 400HV or more.
[0026] [Conductivity (%IACS)] The copper alloy of this embodiment has a conductivity of 8% IACS or more. This allows the copper alloy of this embodiment to be used as a material for various products that require conductivity, such as contact probe pins for semiconductor testing. In addition, since the copper alloy of this embodiment is preferably used for the above-mentioned applications, the equivalent wire diameter is set to 0.5 to 5.0 mm, and it is sufficient for the copper alloy to have a conductivity of 8% IACS or more as its electrical properties, but it may be preferably 10% IACS or more. The conductivity of the copper alloy is measured by a four-terminal method (sample length 100 mm) in a thermostatic chamber at 20°C in accordance with JIS-C3002 "Test Method for Electrical Copper Wire and Aluminum Wire".
[0027] The copper alloy of this embodiment can be manufactured in the same manner as a general alloy wire. For example, first, a copper alloy material having the above-mentioned chemical composition is melted using a continuous casting machine, and a long rod material is manufactured by continuous casting. Next, the rod material is thinned to a predetermined wire diameter by repeatedly performing, for example, annealing and cold wire drawing, thereby manufacturing a long copper alloy (wire material). EXAMPLES
[0028] More specific examples of the present invention will be described below, but the present invention is not limited to these examples.
[0029] Copper alloy materials having the chemical compositions shown in Table 1 were melted and continuously cast using a continuous casting machine to produce rod materials. The rod materials were then annealed and cold drawn at least twice to produce copper alloy wire materials with equivalent wire diameters in the range of 1.0 to 5.0 mm. Annealing was performed at a temperature in the range of 600°C to 1000°C.
[0030] The copper alloy wire was evaluated for electrical conductivity, Vickers hardness, and production yield.
[0031] Furthermore, pins for contact probes were manufactured using the above copper alloy wire, and a continuous conductivity test (burn-in test) was performed on these pins in an atmosphere at a temperature of 250°C. In the continuous conductivity test, these pins were continuously brought into contact with and out of contact with the inspection surface of a silicon wafer 10,000 times. Then, the condition of the pins after the test (presence or absence of defects, etc.) was evaluated.
[0032] Table 1 shows the chemical compositions and evaluation results of the copper alloys of the invention and the comparative materials.
[0033] [Table 1]
[0034] [Invention materials] As is clear from Table 1, the inventive materials 1 to 30 have a Vickers hardness of 350HV or more and a conductivity of 8%IACS or more, and it was confirmed that they have excellent hardness and conductivity. Furthermore, for any of the inventive materials, no breakage or breakage occurred during the production and processing of long objects such as wires, and no defects such as scratches were found on the surface or inside of the wires after processing. Furthermore, the pins of the contact probes manufactured using the inventive materials did not experience any defects such as cracks, defects, or thermal deformation during the continuous conductivity test.
[0035] [Comparative material 1] Comparative material 1 is an example that does not satisfy the contents of the chemical components specified by the present invention with respect to Ni, Si, Sn, and B, and does not satisfy the relative ratio. Specifically, comparative material 1 is an example in which less Ni, more Si, less Sn, and more B are added, and the value of the relative ratio is also small. It can be seen that such comparative material 1 has a satisfactory electrical conductivity, but does not obtain sufficient Vickers hardness. In addition, since the value of the relative ratio is small, disconnection occurred due to the influence of precipitates during the processing into wire. In addition, after the continuous electrical conductivity test, a defect was confirmed at the pin tip of the contact probe pin manufactured using comparative material 1. FIG. 2 shows an enlarged photograph of the pin tip of comparative material 1 after the continuous electrical conductivity test. It was confirmed that the defect at the pin tip occurred due to the presence of precipitates with a particle size of about 10 μm to about 17 μm.
[0036] [Comparative material 2] Comparative material 2 satisfies the numerical range of the relation ratio specified by the present invention, but the content of Si, Sn, and B, which is the premise of the ratio, is outside the range specified by the present invention. Specifically, comparative material 2 is an example in which less Si, more Sn, and more B are added. Comparative material 2 has a slightly higher Vickers hardness than comparative material 1, but does not reach 350 HV, and it was confirmed that the electrical conductivity is also low. In addition, comparative material 2 did not break or break during the production process, but the pin of the contact probe using comparative material 2 had a crack as shown in FIG. 3 near the tip of the pin (contact point with the silicon wafer) after the continuous electrical conductivity test.
[0037] [Comparative material 3] Comparative material 3 is an example that does not satisfy the contents of chemical components specified by the present invention with respect to Si and B, and does not satisfy the relative ratio. Specifically, comparative material 3 is an example in which Si is small, Sn is large, and B is added in large amounts, and the value of the relative ratio is small. It was confirmed that comparative material 3 has low electrical conductivity and Vickers hardness. It was also confirmed that comparative material 3 had material breakage during and after wire drawing and after continuous electrical conductivity testing. When the cross section of comparative material 3 was observed in more detail, it was confirmed that several voids a (micropores) with a width of about 10 to 350 μm were formed inside the cross section, as shown in FIG. 4. It was also confirmed in FIG. 5 that voids a with a width of 10 to 50 μm were generated in various places on the material surface. It is presumed that the material breakage occurred from these voids a.
[0038] [Comparative material 4] Comparative material 4 is an example that does not satisfy the contents of chemical components specified by the present invention with respect to Si, Sn, and B, and does not satisfy the relative ratios either. Specifically, comparative material 4 is an example in which a small amount of Si, a large amount of Sn, and a large amount of B are added, and the relative ratios cannot be calculated. In comparative material 4, breakage occurred during wire drawing. Furthermore, in the contact probe pin using comparative material 4, cracks occurred as shown in Figure 3 in the continuous conductivity test, similar to comparative material 2.
[0039] [Comparative material 5] Comparative material 5 satisfies the numerical range of the relational ratio specified by the present invention, but the content of Al and Sn, which is the premise of the relational ratio, is outside the range specified by the present invention. Specifically, comparative material 5 is an example in which the content of Al is small and the content of Sn is large. Comparative material 5 has sufficient electrical conductivity, but does not have sufficient Vickers hardness. Furthermore, although comparative material 5 did not suffer from disconnection or breakage during the production process, a continuous electrical conductivity test confirmed that the contact probe pin was thermally deformed, making continuous use difficult.
[0040] [Comparative material 6] Comparative material 6 contains beryllium and is an example that does not meet the chemical composition and related ratios specified by the present invention. Comparative material 5 had sufficient electrical conductivity and Vickers hardness, but broke due to the presence of precipitates during processing into wire, just like comparative material 1. In addition, a contact probe pin was made from comparative material 5, and a continuous electrical conductivity test was carried out, confirming that the tip was chipped as shown in Figure 2, just like comparative material 1.
[0041] As is clear from the above considerations, it has been confirmed that in order to solve the problems of the present invention, it is important to satisfy both the contents and the relative ratios of the chemical components of the present invention. [Explanation of symbols]
[0042] 1 Contact Probe 2 pin
Claims
1. A copper alloy in a long form having an equivalent wire diameter of 0.5 to 5.0 mm, In mass%, the alloy contains 9.00%≦Ni≦15.00%, 0.30%≦Si≦0.90%, 0.50%≦Al≦2.00%, 2.00%<Sn≦4.50%, 0%<B<0.010%, and the balance is Cu and inevitable impurities; Vickers hardness is 350 HV or more, The electrical conductivity is 8% IACS or more; The relative ratios of Si, Al, Sn and B satisfy 120≦(1.7Si+1.2Al+Sn) / 3.9B≦300; Copper alloy.
2. The copper alloy of claim 1 comprising, by weight, 11.00%≦Ni≦15.00%, 0.40%≦Si≦0.90%, and 1.00%≦Al≦2.00%.
3. 3. The copper alloy according to claim 1, wherein the relationship ratio satisfies 160≦(1.7Si+1.2Al+Sn) / 3.9B≦250.
4. A pin for a contact probe, which uses the copper alloy according to claim 1 or 2.
Citation Information
Patent Citations
Multi-element Cu-Ni-Sn-based alloy for oil and gas exploitation and preparation method thereof
CN115786766A
Method for mounting thermo-conductive plate, pipe for solar energy and hot floor heat having useful thermo- conductive characteristic in solar energy radiation part, hot floor part, in particular metallic member of various shapes, i.e. energy saving solar heat, hot floor heat collection, ground surface and building, already-installed dwellings
JP1982043165A
Copper alloy ingot and copper alloy material excellent in cutting workability, and copper alloy parts using the same
JP2012046812A
High strength wear resistant multicomponent copper alloy
JP2022182908A
Copper alloy extra-fine wire for springs and its manufacturing method
JP7145070B2